2009
DOI: 10.1038/bmt.2009.227
|View full text |Cite
|
Sign up to set email alerts
|

Early thrombin generation and impaired fibrinolysis after SCT associate with acute GVHD

Abstract: The evolution of coagulation and fibrinolysis has not been thoroughly evaluated in allogeneic SCT. In this pilot study, we characterized the adaptive mechanisms of coagulation and fibrinolysis during allogeneic SCT and 3-month followup and studied possible associations with outcome, including acute GVHD. Thirty patients underwent SCT for a haematological malignancy after myeloablative conditioning. Nineteen patients received the transplant from an HLAidentical sibling and 11 from an unrelated donor. GVHD proph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 26 publications
0
21
2
Order By: Relevance
“…The mortality rate of patients with hemorrhagic complications was found to be 25% higher than in patients who did not bleed [9]. It has been reported that upregulated thrombin generation and fibrinolysis inhibition occur in one-third of allo-HSCT patients and that this is associated with the development of aGVHD [10]. These findings suggest an interplay between coagulation and immunology following allo-HSCT.…”
Section: Discussionmentioning
confidence: 64%
“…The mortality rate of patients with hemorrhagic complications was found to be 25% higher than in patients who did not bleed [9]. It has been reported that upregulated thrombin generation and fibrinolysis inhibition occur in one-third of allo-HSCT patients and that this is associated with the development of aGVHD [10]. These findings suggest an interplay between coagulation and immunology following allo-HSCT.…”
Section: Discussionmentioning
confidence: 64%
“…On the other hand, increased tPA levels have been reported during sepsis in mice and the early phase of HSCT in humans. 5,[47][48][49] We found that plm is activated during the early phase of aGVHD and endotoxin shock, causing severe tissue destruction. YO-2 can block excessive circulating plm thereby blocking fibrinolysis, without the requirement of binding to the lysine-binding site of the plg molecule-binding fibrin as other plm inhibitors.…”
Section: Discussionmentioning
confidence: 97%
“…3 The 'cytokine storm' drives the systemic inflammatory response observed in septic shock and aGVHD, accelerates the coagulation/fibrinolytic system and generates an imbalance between coagulation and fibrinolysis. 4,5 Plasmin (plm), a serine protease, is generated by conversion from plasminogen (plg) by two plasminogen activators (PA), such as tissue-type PA (tPA) and urokinase-type PA (uPA). Although tPA has a dominant role in the resolution of fibrin clots (fibrinolysis), uPA can activate extracellular proteolysis during inflammatory processes.…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that the risk for TAC includes many factors, such as age of the patient, basal disease or the degree of disease remission before HSCT [7,8]. Additionally, previous reports have documented the effect of conditioning regimens that included TBI or not [9].…”
Section: Stem Cell Research and Therapymentioning
confidence: 99%